2016
DOI: 10.1007/s00266-016-0744-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipoinjection and Multiple Internal Cuts for Congenital Constriction Bands: A New Treatment Approach

Abstract: BackgroundTraditional treatment for a congenital constriction band of the limb involves multiple Z-plasties and W-plasties. We propose an alternative surgical procedure for the treatment of congenital constriction bands that obviates the need for Z-plasties and eliminates the constriction band.MethodsWe present the case of a 36-year-old woman with a congenital constriction band of the leg. Using a minimally invasive approach, the skin segment that included the band was dissected from the deep tissues. Afterwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Based on the haphazard nature of the constriction, the patient most likely has amniotic band sequence (ABS), or congenital constriction bands. Amniotic band sequence is a primarily sporadic disorder that affects approximately 1 in 1500‐15 000 births …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the haphazard nature of the constriction, the patient most likely has amniotic band sequence (ABS), or congenital constriction bands. Amniotic band sequence is a primarily sporadic disorder that affects approximately 1 in 1500‐15 000 births …”
Section: Discussionmentioning
confidence: 99%
“…ABS includes a variety of congenital anomalies that are due to constriction rings formed by fibrous amniotic bands because of early intrauterine rupture of the amniotic sac . Constriction bands of varying depth can lead to anomalies that range from circumferential constriction bands around extremities or digits to more severe defects such as syndactyly, pseudoainhum, club feet, body wall defects, and craniofacial abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Autologous facial fat injection is an excellent therapeutic resource in craniofacial and cosmetic surgery. [3,4,5] Autologous fat is a suitable alternative for nasal modeling because of four factors: ease of collection, compatibility, the temporality of the results, and safety. In this sense, various authors have reported good results using fat grafts for nasal modeling in cases such as radix complex, increased height of the nasal dorsum, saddle deformity, post-traumatic sequelae, etc.…”
Section: Accepted Manuscriptmentioning
confidence: 99%